Development of Machine Vision System for Detection of Wrap-Around in n-TOPCon Solar Cells - Kim, Junhee; Kim, Han-Jung; Ko, Yohan; Kim, Yoonkap (2023 IEEE 50th Photovoltaic Specialists Conference (PVSC), 2023)
n-TOPCon solar cells have been the subject of extensive research by various groups in order to overcome the limitations on efficiency of p-PERC solar cells. The passivated contacts formed on the rear side of wafers for the production of n-TOPCon solar cells are deposited using LPCVD or PECVD, however, wrap-around of heavily doped polysilicon is inevitable and results in optical loss and increased shunt resistance. Therefore, post-etching process of wrap-around is necessary and detection of wrap-around after the etching process is also required. In this study, we report on the development of a machine vision system based on a digital microscope equipped with a high-magnification zoom lens and controlled by operation software to minimize human intervention as much as possible. Although further optimization of the machine vision system is needed, we expect to achieve meaningful results after optimization.